The Performance Evaluation of stck Portofolios Formed Using Accounting and Market Data in Jakarta stock Exchange - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
This study evaluates performance of various stocks portfolios that are formed with the use of accounting and market data such as Price Earnings Ratio (PER), Price to Book Value (PBV), Price to Sales Ratio (PSR), and Return on Equity (ROE) in the Jakarta Stock Exchange over the period of 1993 to 1998. Each portfolio consists of 25 equally weighted stocks and is formed based on the level of PER, PBV, PSR, and ROE. The portfolio is also categorized based on their market capitalization. Various measures of performance are employed to evaluate the portfolios. The results show that the performance of portfolios with low PER, PBV, and PSR is ntuch better than that of high PER, PBV, and PSR. Further, the performance of large capitalization portfolios generally is worse than that of other portfolios. portfrolios with high ROE tend to perform well, regardless of their capitalization. Our findings suggest that investors can generate superior returns by employing accounting market information. The results may also indicate some form of market inefficiency in the Jakarta Stock Exchange. Keywords: Jakarta Stock Exchange